2016
DOI: 10.1007/s11947-016-1755-5
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Tempered Dark Chocolate Using Ultrasonic Spectrometry

Abstract: Ultrasonic spectrometry was used to distinguish between properly tempered and untempered commercial dark chocolate. X-ray diffraction (XRD) and differential scanning calorimetry (DSC) were used to characterize the polymorphic state of tempered and untempered chocolate, results that were correlated to those of ultrasonic spectrometry. Four different kinds of dark chocolate samples with different amounts of sugar (7.5-50 %), fat (30-50 %), and cocoa mass (70-90 %) were subjected to two different tempering protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 29 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…The first X-ray diffraction experiments on TAGs were carried out by the pioneers Clarkson and Malkin in 1934 who were among the first to analyze the polymorphism of TAGs . TAG polymorphism has since been widely studied, applying various methods such as microscopy, infrared and Raman spectroscopies, nuclear magnetic resonance, differential scanning calorimetry, ,, ultrasound measurements, X-ray and neutron scattering methods, , and computer simulations. , We note that TAGsalthough overall nonpolar moleculespossess a slight amphiphilic character, for the glycerol backbone is moderately hydrophilic because of the partial charges of both the oxygen and carbon atoms of the ester bond, whereas the acyl chains are completely hydrophobic . Therefore, they undergo aggregation into ordered structures with repeat distances in the order of few nanometers.…”
Section: Introductionmentioning
confidence: 96%
“…The first X-ray diffraction experiments on TAGs were carried out by the pioneers Clarkson and Malkin in 1934 who were among the first to analyze the polymorphism of TAGs . TAG polymorphism has since been widely studied, applying various methods such as microscopy, infrared and Raman spectroscopies, nuclear magnetic resonance, differential scanning calorimetry, ,, ultrasound measurements, X-ray and neutron scattering methods, , and computer simulations. , We note that TAGsalthough overall nonpolar moleculespossess a slight amphiphilic character, for the glycerol backbone is moderately hydrophilic because of the partial charges of both the oxygen and carbon atoms of the ester bond, whereas the acyl chains are completely hydrophobic . Therefore, they undergo aggregation into ordered structures with repeat distances in the order of few nanometers.…”
Section: Introductionmentioning
confidence: 96%
“…In literature is reported that the main cocoa butter FA are stearic acid (34.62–35.67%), oleic acid (32.18–34.43%), and palmitic acid (25.24–28.41%) [ 46 ]. The differences of the cacao mass FAs profile in literature are mainly explained by the influence of geographical origins, but not by the chocolate processing conditions [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Parameters of the ultrasonic wave, propagating in a liquid, are directly affected by the thermodynamic properties of the liquid, which in turn are functions of pressure and temperature (Winkelmeyer et al 2016). Therefore, by measuring the speed of sound in liquid and ultrasonic attenuation, we can gain valuable information about the thermodynamic properties of the liquid.…”
Section: Speed Of Sound C Measured In the Dag Oilmentioning
confidence: 99%